Development of Geopolymers for Catalyst Support Applications - Vieira,Leo (2019)
A geopolymer with high specific surface area was synthesized from metakaolin, amorphous silica and KOH, in the absence of foaming or saponification agents. The mixture modelling technique was selected for this study among the Design of Experiments tools, using surface area and total pores volume as response variables. The Si/K = 2.46 and Si/Al = 1.37 ratios lead to the optimal experimental conditions, allowing the formation of a geopolymer having a specific surface area of 75 m2/g and total pores volume of 0.28 cm3/g. The pores had a bimodal pore size distribution (7 and 20 nm). In spite of its amorphous nature, this structure is similar to zeolites in terms of ion exchange and metal ions accommodation. Therefore, this study envisages its application as a catalyst support.